MOLECULAR INTERACTIONS OF L-TYROSINE IN DIMETHYL SULFOXIDE AQUEOUS SOLUTIONS. PART 1: ELECTRONIC ABSORPTION AND FLUORESCENCE SPECTROSCOPY STUDIES (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
Molecular interactions of L-tyrosine in dimethyl sulfoxide (DMSO) aqueous solutions have been studied using electronic absorption and fluorescence spectro¬scopy methods. It has been shown that at low concentrations of DMSO in aqueous media hetero-associates such as 1DMSO:1H2O or 1DMSO:2H2O are formed, while at high concentrations, associates of a more complex structure (mixed clusters) are formed that interact with L-tyrosine to form complex compounds.
Keywords: L-tyrosine; dimethyl sulfoxide; electronic absorption spectroscopy; fluorescence spectroscopy